The message of Acts in Codex Bezae : a comparison with the Alexandrian tradition.: a comparison with the Alexandrian tradition. Acts 13.1-18.23 : the ends of the earth, first and second phases of the mission to the gentiles / Vol. 3, (©2007) - Unknown
No abstract available